Electrophoretic chip based on special wettability surfaces for detection of heavy metals - Jiang, Shuyue; Zhang, Haifeng; Wang, Panpan; Li, Zhaoxin (Microchemical journal, 2023)
[Display omitted] •An electrophoretic chip based on special wettability surfaces is designed and fabricated in a simple method.•The special wettability surfaces can achieve the excellent enrichment and effective separation of heavy metals under the action of electric field.•Super-hydrophilic working electrode of MXene/CeO2/PVA displays an excellent detection activity toward heavy metals.•Ultra-low limit of detection (LOD) of the developed electrophoretic chip for Pb2+, Hg2+, Cu2+, and Cd2+ were 0.96, 0.87, 0.80, and 0.97 nM.•The developed electrophoretic chip showed satisfactory recoveries (from 94.8% to 99.7%) of heavy metal ions (Pb2+, Hg2+, Cu2+, and Cd2+) in laboratory water and tap water. Electrophoretic chip coupling to electrochemical detection enables the separation, monitoring, and on-site testing of multiple analytes simultaneously. However, bonding technology and detection sensitivity of the electrophoretic chip have severely diminished its value in industrial production. In this paper, a novel open PDMS/PCB electrophoretic chip based on special wettability surfaces was proposed. The developed chip employs the combination of superhydrophobic surface and super-hydrophilic microchannels to complete the function of bonding technology, avoiding the unreliability of the bonding process. The developed chip applied the super-hydrophilic porous MXene/CeO2/PVA hydrogels electrode, enhancing the sensitivity of chip. Finally, the developed chip was employed to simultaneously detect Pb2+, Hg2+, Cu2+, and Cd2+ in laboratory and tap water via differential pulse voltammetry (DPV). It exhibited excellent performance with a low limit of detection (Pb2+ 0.96 nM, Hg2+ 0.87 nM, Cu2+ 0.80 nM, and Cd2+ 0.97 nM). The features of cost-effectiveness, high-reliability, and high-sensitivity make this electrophoretic chip useful for on-site monitoring of multiple analytes in industrial and medical fields.